Spiritual Benson Relaxation in Reducing Stress in Patients Undergoing Hemodialysis - Tata Mahyuvi; Noer Istiqomah; Yuly Peristiowati; Katmini; Joko Prasetyo; Indasah; Hari Prasetyo Umar (Journal of Nursing Practice, 2023)
Background:  Patients with chronic kidney failure experience various changes in their lives, starting from their diet, exercise, blood sugar control, urea, creatinine and renal function replacement therapy that must be carried out throughout their lives, causing long stress for the patient.